2023
DOI: 10.1002/ddr.22078
|View full text |Cite
|
Sign up to set email alerts
|

Novel ester tethered dihydroartemisinin‐3‐(oxime/thiosemicarbazide)isatin hybrids as potential anti‐breast cancer agents: Synthesis, in vitro cytotoxicity and structure–activity relationship

Abstract: A series of ester tethered dihydroartemisinin‐3‐(oxime/thiosemicarbazide)isatin hybrids 7a–p were designed, synthesized, and assessed for their antiproliferative activity against MCF‐7, MDA‐MB‐231, MCF‐7/ADR, and MDA‐MB‐231/ADR breast cancer cell lines. Among them, hybrids 7a,f (IC50: 1.33–3.84 µM) showed potent activity against triple‐negative (MDA‐MB‐231 and MDA‐MB‐231/ADR) breast cancer cell lines, and hybrid 7f (IC50: 3.90 and 10.18 µM) also demonstrated promising activity against estrogen receptor‐positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Xu et al reported [ 88 , 89 ] a series of dihydroartemisinin–isatin hybrids conjugated through ester linkers of different lengths. In particular, dihydroartemisinin ( 2 ) was reacted with isatin carboxylic acid homologue derivatives 151a – d ( Scheme 28 ) and their C-5 derivatives substituted with fluorine, methyl and methoxy moieties.…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al reported [ 88 , 89 ] a series of dihydroartemisinin–isatin hybrids conjugated through ester linkers of different lengths. In particular, dihydroartemisinin ( 2 ) was reacted with isatin carboxylic acid homologue derivatives 151a – d ( Scheme 28 ) and their C-5 derivatives substituted with fluorine, methyl and methoxy moieties.…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
“…The synthesis of the most potent hybrids of the series 153a – c is reported in Scheme 28 . Hybrid 153a [ 89 ], presenting the shortest linker (two-carbon alkyl chain) and the thiosemicarbazide moiety at the C-3 position of isatin, showed high activity and cytoselectivity, being 53- and 46-fold more potent than parent dihydroartemisinin ( 2 ) towards triple-negative MDA-MB-231 and MDA-MB-231/ADR breast cell lines and 75- and 55-fold more potent than in MCF-7 and MCF-7/ADR cell lines, respectively ( Scheme 28 ). Analogously, hybrid 153b (R = OBn) [ 88 ], with a three-carbon alkyl chain and the benzoxime moiety at the C-3 skeleton of isatin, showed a similar activity profile to that of hybrid 153a ( Scheme 28 ).…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research revealed that the linker between the isatin and dihydroartemisinin moieties was essential for the activity, and the incorporation of 1,2,3-triazole between the two pharmacophores reduced the activity based on the fact that hybrids 7 (IC 50 : 59.8->100 µM) exhibited marginal efficacy against MCF-7/ADR, MDA-MB-231, and MCF-7 BC cell lines, [31] whereas replacement of the ether linker by ester linker was permitted. [32][33][34][35] For the estertethered isatin-dihydroartemisinin hybrids 8, the SARs revealed that (1) the activity was remarkably impacted by the carbon spacer between the isatin and dihydroartemisinin moieties, and a shorter linker was usually more favorable than the longer ones; (2) the activity was boosted up by benzoxime at position C-3 of isatin motif; and (3) electron-donating group at C-5 position of isatin skeleton attenuated the activity. [32][33][34][35] Among them, hybrids 8a,b (IC 50 : 3.85-9.36 and 3.21-9.53 µM, respectively) were approximately ≥8.4 times more potent than dihydroartemisinin (IC 50 : 79.10 and 82.78 µM), artemisinin (IC 50 : >100 µM), and doxorubicin (IC 50 : >100 µM) against multidrugresistant MDA-MB-231/ADR and MCF-7/ADR cell lines.…”
Section: Isatin-dihydroartemisinin Hybridsmentioning
confidence: 99%
“…[32][33][34][35] For the estertethered isatin-dihydroartemisinin hybrids 8, the SARs revealed that (1) the activity was remarkably impacted by the carbon spacer between the isatin and dihydroartemisinin moieties, and a shorter linker was usually more favorable than the longer ones; (2) the activity was boosted up by benzoxime at position C-3 of isatin motif; and (3) electron-donating group at C-5 position of isatin skeleton attenuated the activity. [32][33][34][35] Among them, hybrids 8a,b (IC 50 : 3.85-9.36 and 3.21-9.53 µM, respectively) were approximately ≥8.4 times more potent than dihydroartemisinin (IC 50 : 79.10 and 82.78 µM), artemisinin (IC 50 : >100 µM), and doxorubicin (IC 50 : >100 µM) against multidrugresistant MDA-MB-231/ADR and MCF-7/ADR cell lines. [32] In addition, hybrids 8a,b (IC 50 : >100 µM) were found to have no toxicity against healthy MCF-10A breast cells.…”
Section: Isatin-dihydroartemisinin Hybridsmentioning
confidence: 99%